Thomas Cyrcetur, a Fifteenth-century Theologian and Preacher - Ball, R. M. (The journal of ecclesiastical history, 1986)
Thomas Cyrcetur belonged to the second generation of anti-Wycliffite theologians. He must have been born c. 1376, and was a Fellow of Merton College in 1395 or 1396 and until at least 1401. He had graduated BD by December 1417, and probably left the university for residence in Somerset about 1418/19. The immediate Wycliffite threat had thus passed by the time of his Oxford career, and he was not involved in scholastic polemic against Wyclif. On the other hand, he was little influenced by the new orthodox outlook which developed in the universities and in London from the 1420s onwards. He had left Oxford by the time of the publication of Dr Thomas Walden's (alias Netter's) Doctrinale antiquitatum ecclesie, with its new patristic approach to combating heresy, and he shows no sign of acquaintance with that work, although it achieved immediate success. He had long ceased to reside in the university, and was of advanced years, by the time of the opposition to Bishop Pecock in the 1440s and 1450s, which was led by a group of theologians, many from Cambridge but including some Oxford men, whose approach appears also to have been patristic as well as consciously orthodox, and whose best-known member is Thomas Gascoigne. Cyrcetur's approach to theology remained conservative, but it was also pastoral. Even before he graduated BD he took an interest in pastoral work.